ANALISIS IMPLEMENTASI KEBIJAKAN EARMARKING TAX ATAS PAJAK PENERANGAN JALAN (STUDI KASUS WILAYAH DKI JAKARTA TAHUN 2020-2023 - Andika, Diana Putri; Wahyudin, Dian (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The phenomenon of 53 units of street lighting lights that have died along Sedayu City road, Fly Over Kelapa Gading, Sunter to Plumpang Tanjung Priok road, North Jakarta where the road is a crowded logistics travel area so it will be very dangerous for motorists. This study aims to analyze the Implementation of the Earmarking Tax Policy on Street Lighting Tax in the DKI Jakarta Region and the efforts made in overcoming obstacles in the Implementation of Earmarking Tax on Street Lighting Tax in DKI Jakarta City. The type of research used is a type of descriptive research with a qualitative approach. The data collection techniques used are in the form of interviews, observations, and documentation. The conclusion of the study is that the number of street lighting installation points has decreased, while the realization of street lighting tax revenue has increased by 112.79%, the repair and installation of public street lighting has not been evenly distributed, there is still a lack of supervision, maintenance and lack of supporting infrastructure. Research suggestions are to collaborate between related parties such as PLN where they have the necessary infrastructure, carry out budgeting and infrastructure procurement, and socialize the application of earmarking tax and calculation methods to the community through social activities, festivals and seminars, then collaborate with the sub-district or sub-district level government to conduct socialization to the community